Cluster of Imported Vivax Malaria in Travelers Returning From Peru. Issue 6 (10th September 2015) - Weitzel, Thomas; Labarca, Jaime; Cortes, Claudia P.; Rosas, Reinaldo; Balcells, M. Elvira; Perret, Cecilia
Abstract : We report a cluster of imported vivax malaria in three of five Chilean travelers returning from Peru in March 2015. The cluster highlights the high risk of malaria in the Loreto region in northern Peru, which includes popular destinations for international nature and adventure tourism. According to local surveillance data, Plasmodium vivax is predominating, but Plasmodium falciparum is also present, and the incidence of both species has increased during recent years. Travelers visiting this region should be counseled about the prevention of malaria and the options for chemoprophylaxis.